2020
DOI: 10.1080/10942912.2020.1797784
|View full text |Cite
|
Sign up to set email alerts
|

Functional and instrumental textural properties of reduced-salt meat emulsions with konjac gel: Combined effects of transglutaminase, isolate soy protein, and alginate

Abstract: The functional and instrumental textural properties of reduced-salt meat emulsions (RSMEs) containing konjac gel, with combined transglutaminase (TG), isolated soy protein (ISP), and alginate were investigated to determine optimal quality characteristics. Control groups were produced using 1.2% salt (-) and 1.5% salt (+). RSMEs (1.2% salt) formulations contained T1 (konjac gel), T2 (konjac gel + TG), T3 (konjac gel + ISP), T4 (konjac gel + TG + ISP), T5 (konjac gel + alginate), and T6 (konjac gel + TG + algina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…On the other hand, previous studies had been reported that the addition of konjac gel could increase the hardness of meet emulsion (Yong et al., 2020). Whereas Gibis et al.…”
Section: Resultsmentioning
confidence: 92%
“…On the other hand, previous studies had been reported that the addition of konjac gel could increase the hardness of meet emulsion (Yong et al., 2020). Whereas Gibis et al.…”
Section: Resultsmentioning
confidence: 92%
“…The percentages of additives were based on the total amount of meat, ice, and fat. Flaked ice (250 g) was added to the bowl and homogenized for 1 min at the same knife speed, and then ground fat (250 g) was homogenized together with the ice for 1 min at the same knife speed [ 18 ]. The 25 g of meat emulsion was stuffed into conical tubes and heated at 75 °C for 30 min in water bath (JSSB-30T, JS Research, Gongju, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…To counteract the adverse efects of the reduction of sodium and phosphate on the functional and organoleptic properties of meat emulsions, researchers have currently been looking for alternative components which include edible seaweeds [13], microbial transglutaminase [14,15], soy protein isolate [16], and bamboo salt [6], along with rice and potato starches [17]. Other researchers have been focused on emerging technologies including high hydrostatic pressure (HHP) processing [9] or ultrasound treatments [18] aimed at improving functional properties and minimizing cooking water losses.…”
Section: Introductionmentioning
confidence: 99%